Probing Electronic Properties of CVD Monolayer Hexagonal Boron Nitride by an Atomic Force Microscope - Deng, Shiyu; Gu, Yanyun; Wan, Xi; Gao, Mingliang; Xu, Shijia; Chen, Kun; Chen, Huanjun (Frontiers in Materials, 2021)
Ultrathin hexagonal boron nitride (h-BN) has recently attracted a lot of attention due to its excellent properties. With the rapid development of chemical vapor deposition (CVD) technology to synthesize wafer-scale and single-crystal h-BN, the properties of h-BN have been widely investigated with a variety of material characterization techniques. However, the electronic properties of monolayer h-BN have rarely been quantitatively determined due to its atomically thin thickness and high sensitivity to the surrounding environment. In this work, by the combined use of AFM (atomic force microscope) PeakForce Tunneling (PF-TUNA) mode and Kevin probe force microscopy (KPFM) model, both the electrical resistivity (529 MΩ·cm) and the inherent Fermi level (~ 4.95 eV) of the as-grown monolayer h-BN flakes on the copper substrate has been quantitatively analyzed. Moreover, a direct visualization of the effect of h-BN nanoflakes as a high-temperature oxidation-resistant has been presented. Our work demonstrates a direct estimation of the electronic properties for 2D materials on the initial growth substrate without transfer, avoiding any unwanted contaminations introduced during the transfer process. The quantitative analysis by state-of-the-art AFM techniques implies that monolayer h-BN can be employed as an atomically thin and high-quality insulator for 2D electronics, as well as a high-temperature anti-oxidation layer for electronic device applications.